Design and implementation of interventions to improve unplanned pregnancy experiences: a mixed-methods study protocol with an interventional design - Masoumeh Paiandeh; Roghaiyeh Nourizadeh; Esmat Mehrabi; Mojgan Mirghafourvand; Easa Mohammadi (BMC, 2024)
Abstract Background Unintended pregnancy, a pregnancy that have been either unwanted or mistimed, is a serious public health issue. The present study aims to design and implement interventions to improve unplanned pregnancy experiences. Methods/design This exploratory sequential mixed method study will be conducted in three phases: qualitative, intermediate, and quantitative. The qualitative phase will use qualitative conventional content analysis with in-depth and semi structured individual interviews to explain and define the components and elements of pregnancy experiences of unplanned pregnancies, which include mothers with unplanned pregnancies, their spouses, and prenatal care providers, who will be selected purposefully. Additionally, in the initial phase, the study will employ literature reviews alongside qualitative findings to elucidate the components and elements of pregnancy experiences and their improving interventions. In the second phase, appropriate interventions (prioritized and feasible) will be determined through an expert panel using the Delphi technique. In the third phase, the intervention program agreed upon in the previous phase will be implemented in the form of a randomized controlled clinical trial. Discussion The implementation of the interventions could be beneficial in changing attitudes and achieving positive experiences in unplanned pregnancies. It is anticipated that the design and implementation of the intervention program aimed at improving the experiences of unplanned pregnancies will be effective in minimizing adverse maternal and neonatal outcomes. Trial registration Iranian Registry of Clinical Trials (IRCT): (IRCT20170506033834N12/Date of registration: 2024‑02‑12)